Las humanidades liberadas - Dominique Vinck; Claire Clivaz (Revue d'anthropologie des connaissances)
The special issue attempts to understand what happens to cultures whose expression was linked to the written word and the book by Western modernity. It looks at what is happening to the humanities with digitization and what is happening to the relationship between the humanities and the sociomaterial practices that shaped knowledge and culture. It proposes to reflect on the usual categories of "book" and "outside the book" cultures, how they have been taken into account in the past, their return and reinvention.